Darkening effect on AZ31B magnesium alloy surface induced by nanosecond pulse Nd:YAG laser - Guan, Y.C. (2016)
Permanent darkening effect was achieved on surface of AZ31B Mg alloy irradiated with nanosecond pulse Nd:YAG laser, and special attention was made to examine how surface structure as well as oxidation affect the darkening effect. Experiments were carried out to characterize morphological evolution and chemical composition of the irradiated areas by optical reflection spectrometer, Talysurf surface profiler, SEM, EDS, and XPS. The darkening effect was found to be occurred at the surface under high laser energy. Optical spectra showed that the induced darkening surface was uniform over the spectral range from 200 nm to 1100 nm. SEM and surface profiler showed that surface morphology of darkening areas consisted of large number of micron scale cauliflower-like clusters and protruding particles. EDS and XPS showed that compared to non-irradiated area, oxygen content at the darkening areas increased significantly. It was proposed a mechanism that involved trapping of light in the surface morphology and chemistry variation of irradiated areas to explain the laser-induced darkening effect on AZ31B Mg alloy.